The swamp peddlers : how lot sellers, land scammers, and retirees built modern Florida and transformed the American dream - Vuic, Jason, 1972- (The University of North Carolina Press, 2021)
"Florida has long beckoned retirees seeking to spend their golden years in the sun, but, for many, the American dream of owning a home there was financially impossible. That changed in the 1950s, when the so-called 'installment land sales industry' appeared out of nowhere to hawk billions of dollars of Florida residential property, sight unseen, to retiring northerners. As Jason Vuic recounts in this raucous history, these communities allowed generations of northerners to move to Florida cheaply, but at a price: high-pressure sales tactics begat fraud; poor urban planning begat sprawl; developers cleared forests, drained wetlands, and built thousands of miles of roads in grid-like subdivisions, which, fifty years later, played an inordinate role in the 2008 subprime mortgage crisis"--